INCLUSION IN UKRAINE: MODERN CHALLENGES - Machynska, Nataliia; Blikhar, Viacheslav; Osikowicz, Żanna (Socio-economic relations in the digital society, 2024)
The article is devoted to a theoretical and practical analysis of the problem of inclusion: formation and development, features of educational inclusion, and mechanisms of implementation of inclusive higher education. Based on the analysis of regulatory documents and scientific research, the authors determine the most significant stages of the formation and development of inclusion in Ukraine. The requirements for specialists needed by the modern domestic education system have been analyzed. The article emphasizes the trends in the process of invalidation of the population of Ukraine. The authors determine the expediency and necessity of wide implementation of educational inclusion in the system of higher education, in particular: ensuring free access of all higher education applicants to educational and methodical materials and creating the necessary special units. On the basis of the analysis of the results of the conducted survey, the possible ways of solving the current problems of educational inclusion in the higher education system are substantiated and characterized: support of the teaching staff in the organization of an inclusive educational environment in the institution of higher education; support for education seekers who belong to the category of persons with special needs; financing and implementation of regulated and guaranteed mechanisms for financial support of higher education institutions; technical and methodological support of the educational process. Also, emphasis is placed on electronic inclusion, which is interpreted as a social movement aimed at overcoming the digital divide among different categories of the population. It was found that the appropriate level of organization of an inclusive educational environment is observed in institutions of general secondary education. Instead, HEIs need more active involvement of specialists, technical equipment and financial support for effective educational inclusion. An important factor is the availability of computer equipment: ensuring access to free or low-cost computers, in particular through the implementation of special target programs, charity projects, etc. It is also relevant to search and exchange data to diversify the ways of obtaining education for persons with special educational paths, to ensure effective interpersonal communication despite temporal and spatial boundaries.
Keywords: inclusion; educational inclusion; e-inclusion; higher education; inclusive educational environment; students with special educational needs